Monitoring Symptoms in COVID-19 Patients Following Favipiravir Treatment: Medication Adherence and Adverse Drug Reactions through Telepharmacy Services - Sangrudsamee , Jirawan; Thiplui, Natnicha; Muangruk, Natenapa; Sundaranaga, Rujirat; Chumphoo-in, Chopaka (Journal of Health Science of Thailand, 2026)
This study aimed to examine the symptoms of patients infected with coronavirus disease 2019 (COVID-19) after receiving favipiravir, assessed medication adherence, adverse drug reactions, and managed health issue through the process of telepharmaceutical care. It was a descriptive cross-sectional study conducted between 15 and 31 March 2022, involving 510 COVID-19 patients who received favipiravir from Tron Hospital. Data were collected from medical records and telephone interviews; and were analyzed using descriptive statistics and logistic regression. The majority of participants were female (51.8%), with an average age of 40.1 years. A total of 164 patients (32.2%) were classified as being at risk for severe disease. The results showed that within the first 2–3 days after taking favipiravir, 330 cases (64.7%) reported improvement or feeling well. Problems with incorrect medication use were found in 15 patients (2.9%), and inappropriate use in 4 patients (0.8%). Factors associated with the occurrence of symptoms after medication included age group and the presence of symptoms before starting treatment. Patients aged 15–60 years had a 2.1 times higher risk of developing symptoms compared to those under 15 years (OR=2.1; 95% CI: 1.1–4.2; p=0.029). Those who had symptoms before taking the medication were 7.6 times more likely to experience symptoms afterward compared to asymptomatic patients (OR=7.6; 95% CI: 2.3–24.5; p=0.001). Most patients did not experience adverse drug reactions (92.9%). The most common adverse reactions were diarrhea (4.5%), nausea (1.4%), and a change in eye color to purple or blue (0.6%). Additionally, telepharmaceutical care was found to promote medication adherence, enhance communication between patients and healthcare personnel, and reduce the risk of mortality.